Efficacy of Licorice as Adjunctive Therapy in Critically Ill Patients with COVID-19: A Randomized, Placebo-Controlled, Double-Blind Clinical Trial - Babak Alikiaie; Seyed Mohammad Hosseinian Shalamzari; Rasool Soltani; Afsaneh Yegdaneh; Sarah Mousavi (Wolters Kluwer Medknow Publications, 2024)
Objective: There is no definitive pharmacological strategy for COVID-19; thus, medicinal herbs can be an appropriate option for COVID-19 management. We investigated the efficacy of a D-reglis® tablet (root extract of licorice) as adjuvant therapy in critically ill patients with COVID-19 at intensive care units (ICUs) of Alzahra Teaching Hospital affiliated with Isfahan University of Medical Sciences, Isfahan, Iran. Methods: In the present double-blind, randomized, placebo-controlled clinical trial, critically ill cases with COVID-19 (n = 52) received a D-reglis® tablet (760 mg) or a placebo tablet for 5 days. The ICU stay length was the primary outcome. The secondary outcome included the changes in oxygen saturation, duration of mechanical ventilation, mortality rate, and Sequential Organ Failure Assessment (SOFA) Score during the study period. Findings: The ICU stay was significantly lower in the licorice group than in the placebo group (P = 0.015). No significant difference was detected between the groups regarding oxygen saturation, SOFA score, duration of mechanical ventilation, and mortality rate. Conclusion: The licorice tablet (D-reglis®) as an adjuvant treatment showed promising results regarding the ICU stay length in critically ill COVID-19 patients. However, further clinical trials with larger sample sizes, further duration of intervention, measurement of inflammatory markers, and further study about the molecular mechanism of the effect of licorice on COVID-19 should be done to obtain more conclusive findings.